2008
DOI: 10.1007/s12105-008-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid Carcinoma with Spindle Cell Change: A Low-grade Lesion Potentially Mistaken for Sarcomatoid Dedifferentiation

Abstract: An unusual case of mucoepidermoid carcinoma (MEC) of intraoral minor salivary gland origin with spindled morphology was presented. A fascicular stream of bland spindle cells from typical MEC areas amounted to more than 70% of the tumor. Spindle population had features consistent with immunohistochemical and ultrastructural profiles of intermediate cells and lacked overexpression of p53 and cyclin D1. There was no difference in the Ki-67 index between two distinct components. Awareness of extensive spindle cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…8,9 MEC with a focal spindle cell component is not uncommonly observed, but MEC with a predominance of spindle cells is rare and has only been documented in a few previous studies. [1][2][3][4] In 1964, Lucas and colleagues published a seminal article describing extensive areas of spindle cell change in MEC, 3 and in 1986, a spindle cell variant with high nuclear grade was described by Love et al 4 It took more than 2 decades until 2 cases of MEC with a predominance of spindle cell morphology reemerged in the literature in English, this time with lowgrade morphology. 1,2 The tumor described by Ide et al 1 in 2008 showed solid and cystic architecture where the former component contained streaming fascicles of neoplastic cells with spindle cell morphology featuring low nuclear grade amounting to more than 70% of the tumor volume.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 MEC with a focal spindle cell component is not uncommonly observed, but MEC with a predominance of spindle cells is rare and has only been documented in a few previous studies. [1][2][3][4] In 1964, Lucas and colleagues published a seminal article describing extensive areas of spindle cell change in MEC, 3 and in 1986, a spindle cell variant with high nuclear grade was described by Love et al 4 It took more than 2 decades until 2 cases of MEC with a predominance of spindle cell morphology reemerged in the literature in English, this time with lowgrade morphology. 1,2 The tumor described by Ide et al 1 in 2008 showed solid and cystic architecture where the former component contained streaming fascicles of neoplastic cells with spindle cell morphology featuring low nuclear grade amounting to more than 70% of the tumor volume.…”
Section: Discussionmentioning
confidence: 99%
“…The spindle cell variant of MEC (spMEC), as the name implies, is predominantly composed of spindle cells and is a rare tumor, with only a few documented cases in the literature. [1][2][3][4] These spMECs were located at the posterior maxillary region, oral cavity, including the floor of the mouth as well as in the submandibular gland. [1][2][3][4] A high proportion of MEC of salivary glands as well as of other organs is known to harbor a t (11;19) translocation, which results in fusion of the MEC translocated 1 (MECT1, also CRTC1) gene on chromosome 19p13 with the mastermind-like 2 (MAML2) gene on chromosome 11q21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On review of the smears only spindle cell component was seen which led to an erroneous diagnosis of myoepithelioma. Neoplastic myoepithelium in salivary gland tumors, is prone to assume a spindle cell configuration and has been reported to undergo dedifferentiation [7] .…”
Section: Discussionmentioning
confidence: 99%
“…More than eight potential variants have been tabulated in a recent review article (1), including unicystic (5), sclerosing (2), oncocytic (2,4), clear cell (6,7), spindle cell (8), goblet cell aggressive (3), psammomatous (9,10) and sebaceous types (11). Among them, the sclerosing variant epitomizes the stromal fibrosis and hyalinization accompanied by a dense infiltrate of lymphoplasmacytic cells with or without eosinophilia (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%